Erişkin Hastada Parotis Bezi Hemanjiomu: Olgu Sunumu - Çobanoğlu, Bengü; Özercan, Mehmet Reşat; Karlıdağ, Turgut (Fırat University, 2007)
Hemanjiom tükrük bezi tümörlerinin yaklaşık %1'ini oluşturan konjenital benign bir tümördür. Genellikle erken çocukluk çağında ortaya çıkan tümör olguların %75'inde doğumdan itibaren mevcuttur. 10 yaşından sonra görülme oranı yalnız %1.5'tur. Kadınlarda erkeklere göre daha sıktır. Parotis hemanjiomları yetişkinlerde ender olarak görülür. 33 yaşındaki erişkin bir kadın hastada sol parotis bezinde saptanan hemanjiom olgusu, az görülmesi nedeniyle ilginç bulunarak sunulmuştur.©2007, Fırat Üniversitesi, Tıp Fakültesi

The hemangioma is a congenital benign tumor which constitutes about 1% of salivary gland tumors. Generally it occurs in early childhood and about 75% are present at birth. Only about 1.5% appear after the age of 10 years. It is predominance in females than males. Parotid hemangiomas in adults are much rare. We have reported hemangioma of left parotid gland in an 33 years famele which is notable for its rare occurence. ©2007, Fırat University, Medical Faculty
Parotid Gland Hemangioma in Adult Patients